Elucidating the Structural and Minimal Protective Epitope of the Serogroup X Meningococcal Capsular Polysaccharide - Pietri, Gian Pietro; Tontini, Marta; Brogioni, Barbara; Oldrini, Davide; Robakiewicz, Stefania; Henriques, Pedro; Calloni, Ilaria; Abramova, Vera; Santini, Laura; Malić, Suzana; Miklić, Karmela; Lisnic, Berislav; et al. (Frontiers in Molecular Biosciences, 2021)
Despite the considerable progress towards the eradication of meningococcal disease with the introduction of glycoconjugate vaccines, previously unremarkable serogroup X has emerged in recent years, recording several outbreaks throughout the African continent. Different serogroup X polysaccharide-based vaccines have been tested in pre-clinical trials, establishing the principles for further improvement. To elucidate the antigenic determinants of the MenX capsular polysaccharide, we generated a monoclonal antibody, and its bactericidal nature was confirmed using the rabbit serum bactericidal assay. The antibody was tested by inhibition enzyme-linked immunosorbent assay and surface plasmon resonance against a set of oligosaccharide fragments of different lengths. The epitope was shown to be contained within 5 to 6 α-(1-4) phosphodiester mannosamine repeating units. The molecular interactions between the protective monoclonal antibody and the MenX capsular polysaccharide fragment were further detailed at atomic level by saturation transfer difference NMR spectroscopy. The NMR results were used for validation of the in silico docking analysis between the X-ray crystal structure of the antibody (Fab fragment) and the modeled hexamer oligosaccharide. The antibody recognizes the MenX fragment by binding all 6 repeating units of the oligosaccharide via hydrogen bonding, salt bridges and hydrophobic interactions. In vivo studies demonstrated that conjugates containing 5-6 repeating units can produce high functional antibody levels. These results provide an insight on the molecular basis of MenX vaccine-induced protection and highlights the requirements for the epitope based vaccines design.